Selectivity by planktivorous fish at different prey densities, heterogeneities, and spatial scales. (9th January 2014) - Maszczyk, Piotr; Gliwicz, Z. Maciej
Abstract : Studies in artificially confined, small‐scale experimental systems with a homogeneous prey distribution suggest that selectivity in planktivorous fish for more conspicuous and rewarding prey (such as adult Daphnia with eggs in the brood cavities) is stronger at high than at low prey population density. We examined whether prey selectivity is altered when fish are allowed to feed in larger scale systems and on more heterogeneously distributed prey. The experimental system was comprised of 1000 liter tanks (one, four, or eight), interconnected to allow free movement of roach ( Rutilus rutilus, eight per tank), with different densities of Daphnia prey, distributed with varying levels of homogeneity. As reported previously, the selectivity of roach increased at higher Daphnia densities, but only in small‐scale systems where prey distribution was homogeneous. However, the opposite was found in large‐scale systems with heterogeneous prey distribution, i.e., greater selectivity at lower prey densities. The reversed slope of the selectivity‐on‐prey‐density regression was linked to increased swimming speed at low prey density, where the fish, less constrained by the limited size of the experimental system, accelerate, possibly in an effort to compensate for low encounter rate and to more rapidly locate patches of prey. More selective feeding on scarce and patchy prey may result from the decreased relative visibility of smaller prey and from the increased capture costs due to the need to expend more energy for postcapture accelerations to regain a higher speed.